Catalyzing the Global Energy Transition Through Coconut Biomass Valorization: Exploring Multidimensional Impacts and Opportunities of Allam Cycle Power Systems for Clean and Sustainable Energy Growth - Yajri, Ghifari Jauhar; Ridwansyah, Dzaky Fariz; Raharjo, Alief Amiruddin (Jurnal Global Ilmiah, 2025)
Following Indonesia’s commitment to achieve Net Zero Emissions by 2060, Indonesia’s National Energy Policy (KEN), stated in Government Regulation No. 79 of 2014, is being revised to integrate New Renewable Energy into the national energy mix, targeting 25–26% by 2030 and 70–72% by 2060. Leveraging abundant natural resources, this initiative seeks to reduce carbon emissions through nature-based solutions. This study examines the thermodynamic, economic, and environmental performance, alongside ammonia production potential, of an integrated system using literature reviews validated through Aspen Plus simulations and lifecycle modeling. Results show coconut biomass offers 43.96% energy efficiency and a heating value of 17.54 MJ/kg, producing 157.73 MW from a 200 MW input. Techno-economic modeling revealed a net present value (NPV) of USD 462.388 million, outperforming natural gas-based Allam Cycle systems with an NPV of USD 232 million (NYISO). The proposed system also achieves lifecycle negative emissions of ?0.7445 kgCO?/kWh versus 0.167 kgCO?/kWh for natural gas, underscoring environmental superiority and near-carbon neutrality. By capturing 100% of CO? while maintaining strong economic feasibility, this approach addresses emissions and cost challenges inherent in fossil-fuel-based systems, offering a scalable pathway to sustainable energy growth.